Transcriptome of turbot, sea bream and sea bass in response to nodavirus infection - Novoa, Beatriz; Dios, S.; Poisa Beiro, Laura; Park, Kyoung; Nerland, Audun H.; Brown, Laura L.; Johnson, Stewart; Sarropoulou, Elena; Kotoulas, Georgios; Figueras Huerta, Antonio (2010)
8th International Symposium on Viruses of Lower Vertebrates, Santiago de Compostela (España), 26-29 abril 2010 No